(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2010)
A retrospective study was carried out on 50 patients at Paediatric cardiology unit of Combined Military Hospital, Dhaka to analyze the outcome of balloon angioplasty of coarctation of aorta. The study period extended over two years starting from January 2007. Age of the patient varies from 7 days to 28 years. Twenty two (44%) patients were female and rests were male. Native coarctation was in 44 cases (88%) and post surgical re-coarctation was in 5 cases (10%). Neonatal critical coarctation was 19 (38%). Twelve (24%) cases were detected when they were investigated for hypertension. Abdominal coarctation was found in 6 cases (12%). Multiple coarctations were found in 3 (6%) cases. Two cases (4%) had balloon angioplasty twice as they developed re-coarctation. No intra-operative or post-operative complication was observed in any cases of this series. Data were collected by chart review. No test was performed on any of the subjects as part of study protocol. Coarctation balloon angioplasty of coarctation of aorta is a safe and effective measure to treat coarctation of aorta. Key words: Balloon angioplasty; coarctation of aorta. DOI: 10.3329/jafmc.v6i1.5983 Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.4-7